The Effect Of Transformational Leadership On Political Skill With Organizational Commitment As A Moderating - Azhari Ramadhan; Wahyu Eko Pujianto (Journal Informatic, Education and Management (JIEM), 2025)
This study aims to analyze the effect of transformational leadership on political skills with organizational commitment as a moderating variable. This study departs from the need for political parties for human resources who are not only loyal but also competent in building social influence and strategic networks. The research method applies a quantitative approach through a survey technique to 29 Tidar administrators in Sidoarjo Regency. Data processing was carried out using the Partial Least Square (PLS) method using SmartPLS 4.0 software. The research findings show that transformational leadership and organizational commitment have a positive and significant effect on political skills. However, the relationship between transformational leadership and organizational commitment does not show a significant impact on political skills. This finding confirms the significance of the role of inspiring leadership style and emotional commitment of members in shaping socio-political skills, although both do not support each other simultaneously. This study provides theoretical contributions to the development of leadership literature and interpersonal skills in political organizations, as well as practical impacts to improve the quality of leadership and loyalty of party members.